2014
DOI: 10.1007/jhep07(2014)018
|View full text |Cite
|
Sign up to set email alerts
|

F-theory family unification

Abstract: We propose a new geometric mechanism for naturally realizing unparallel three families of flavors in string theory, using the framework of F-theory. We consider a set of coalesced local 7-branes of a particular Kodaira singularity type and allow some of the branes to bend and separate from the rest, so that they meet only at an intersection point. Such a local configuration can preserve supersymmetry. Its matter spectrum is investigated by studying string junctions near the intersection, and shown to coincide,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 166 publications
0
11
0
Order By: Relevance
“…3 See, e.g. [48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76] for discussions of F-theory on elliptic fibrations with a global section. 4 When F-theory is compactified on a Calabi-Yau genus-one fibration Y , the discrete gauge group arising in this compactification is identified with the discrete part of the "Tate-Shafarevich group," X(J(Y )), of the Jacobian, J(Y ) [47,19].…”
Section: Introductionmentioning
confidence: 99%
“…3 See, e.g. [48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76] for discussions of F-theory on elliptic fibrations with a global section. 4 When F-theory is compactified on a Calabi-Yau genus-one fibration Y , the discrete gauge group arising in this compactification is identified with the discrete part of the "Tate-Shafarevich group," X(J(Y )), of the Jacobian, J(Y ) [47,19].…”
Section: Introductionmentioning
confidence: 99%
“…12 The correspondence between the types of the singular fibers of the elliptic fibration and non-Abelian gauge symmetries forming on the 7-branes in F-theory is discussed in [3,65]. 13 Methods to determine the singular fibers of the elliptic surfaces are described in [68,69]. 14 The cubic curves in P 2 have 10 dimensions, and among these the cubic curves that pass through the seven points that are blown up to yield the degree two del Pezzo surface have 10 − 7 = 3 dimensions.…”
Section: Concluding Remarks and Open Problemsmentioning
confidence: 99%
“…The rank of the group formed by the set of the global sections of the compactification space -or the "Mordell-Weil group"-yields the number of U (1) factors forming in F-theory on the space [3]. The rank 1 Recent studies of F-theory models on elliptic fibrations that admit a global section can be found, for example, in [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their hierarchical mass structures generated by the Higgs mechanism via their corresponding Yukawa couplings strongly suggest the existence of a hidden structure of nature. There are many attempts to understand the origin of chiral generations and/or their hierarchical masses structures by considering e.g., so-called horizontal symmetry (or family symmetry) in four-dimensional (4D) theories [1][2][3][4][5][6][7], geometrical structures in higherdimensional theories [8][9][10] and string theories [11][12][13].…”
Section: Introductionmentioning
confidence: 99%